2015
DOI: 10.1063/1.4931630
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of hydrogen adsorption on Ca-decorated C48B12 clusters

Abstract: The hydrogen adsorption on Ca-decorated C 48 B 12 clusters is studied using density functional theory. The favorable binding site for Ca atom is the hexagonal C 4 B 2 rings. The strong interaction between Ca atoms and C 48 B 12 cluster hinders the aggregation of Ca atoms on the cluster surface. C 48 B 12 is an electron deficient system with a large electron affinity of 2.952 eV. The decorated Ca atoms transfer their electrons to the cluster easily. The net charges on the Ca atoms are in the range of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The hitherto known lowest energy structure consists of 6 homogeneously distributed Ca atoms on the H-sites of the diluted configuration [13] [14]. We found a new structure based on a diluted fullerene that is 0.73 eV lower than the previously predicted configuration.…”
Section: B Camentioning
confidence: 55%
See 1 more Smart Citation
“…The hitherto known lowest energy structure consists of 6 homogeneously distributed Ca atoms on the H-sites of the diluted configuration [13] [14]. We found a new structure based on a diluted fullerene that is 0.73 eV lower than the previously predicted configuration.…”
Section: B Camentioning
confidence: 55%
“…found that homogeneously dis-tributing 6 Ca atoms on the fullerene is stable with respect to decomposition into the fullerene molecule and Ca bulk metal [13]. Most recently a similar study was conducted by Qi et al on the same 6 Ca atom decorated diluted configuration to study the hydrogen uptake mechanism [14]. Lee et.…”
Section: Introductionmentioning
confidence: 94%
“…All the geometry optimization of ground states and transition states (TSs) were carried out through a high quantum level of DFT-D (Dispersion-corrected Density Functional Theory) approach implemented in the DMol 3 program package [28,29]. In this work, the PBE (Perdew, Burke and Ernzerhof) functional [30] with Grimme's longrange dispersion correction [31] (PBE-G) was used.…”
Section: Methodsmentioning
confidence: 99%